Biomarcadores associados ao estresse em cuidadores de crianças com necessidades especiais de saúde - Corrêa, Letícia Patrice Mancini (Universidade Federal de São Carlos, 2023)
Objective: to synthesize and analyze the scientific evidence available in the literature about biomarkers associated with stress in caregivers of children with special health needs. Method: integrative literature review using the PICO strategy in MEDLINE databases; Cochrane Library; BASE; CINAHL; APA PsycINFO; Web of Science and SCOPUS, in addition to manual searches in different sources such as: Clinical Trial; The British Library; Google Scholar and medRxiv, and secondary searches by cross-reference between May and July 2021. Results: sample composed of seven studies, one published in 2011 and the rest between 2017 and 2020. Most (four) of the studies had a case-control design , six studies used saliva samples to assess biomarkers. The analyzed biomarkers were cortisol and alpha amylase. Final considerations: in general, the analyzed articles indicated that the production of cortisol is significantly lower among the care of children with special health needs. It is important to invest in clinical trial-type studies in order to test interventions that can minimize stress in this population.
Biomarkers associated with stress in caregivers of children with special health nedds
Keywords: Enfermagem pediátrica; Criança; Estresse; Biomarcadores; Cortisol; CIENCIAS DA SAUDE::ENFERMAGEM